2000
DOI: 10.1137/s0036141099351176
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Expansions of Symmetric Standard Elliptic Integrals

Abstract: Symmetric standard elliptic integrals are considered when one of their parameters is larger than the others. Distributional approach is used for deriving five convergent expansions of these integrals in inverse powers of the respective five possible asymptotic parameters. Four of these expansions involve also a logarithmic term in the asymptotic variable. Coefficients of these expansions are obtained by recurrence. For the first four expansions these coefficients are expressed in terms of elementary functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…They extend to the complex case the known methods given in [27], [28, chap. 6], [13], [14] for real parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They extend to the complex case the known methods given in [27], [28, chap. 6], [13], [14] for real parameters.…”
Section: Discussionmentioning
confidence: 99%
“…4.4] we can find asymptotic expansions of (10)(a) for large and small z. In the remaining of the paper we use Wong's definition (11)- (13) and consider the method constructed from this definition [28, chap. 6].…”
Section: Jomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our study [23] showed that the series expansion method for computing F (ϕ|m) is significantly slower than: (1) Carlson's duplication method [12,37], (2) Bulirsch's el1 based on the descending Landen transformation [3], and (3) our half argument transformation method [23]. On the other hand, recent research on the series expansions of the symmetric and classic elliptic integrals is instead emphasized to study the behavior of the integrals near their logarithmic singularities at x = 0 and/or y = 0 [13,14,30,31,20,29,28]. …”
Section: Existing Researches On Series Expansions Of Elliptic Integralsmentioning
confidence: 99%
“…Carlson and his collaborators (see [12,13,[15][16][17][18]20,32]) and other researchers (see [21][22][23]). All members of this family of integrals are homogeneous functions of two or three or four variables and they enjoy the symmetry in two or more variables.…”
Section: Introduction and Definitionsmentioning
confidence: 99%